2021
DOI: 10.1007/s40122-021-00339-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Preoperative Ultrasound-Guided Erector Spinae Plane Block on Chronic Postsurgical Pain After Breast Cancer Surgery: A Propensity Score-Matched Cohort Study

Abstract: Breast cancer surgery (BCS) is associated with high incidence of chronic postsurgical pain (CPSP), which may become a heavy burden to the patient.Erector spinae plane block (ESPB) has been applied as a new technique for analgesia in BCS patients.We hypothesized that preoperative singleshot ESPB could reduce the incidence of CPSP at 1 year following BCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…In our study, we found that 34.5% of patients with chronic pain (19.4% of all the patients) showed a neuropathic characteristic with the ID-Pain method. 19,20 Similarly, a comparable prevalence (25%) had been reported by Mongardon N. 20 Moreover, we learned that 47.1% of patients who suffered moderate and severe pain 1 month after the surgery had neuropathological agony, whereas only 10.6% of patients with mild pain had that. Meanwhile, among 29 patients who had neuropathological pain, 28 still suffered 6-month postoperative agony.…”
supporting
confidence: 82%
“…In our study, we found that 34.5% of patients with chronic pain (19.4% of all the patients) showed a neuropathic characteristic with the ID-Pain method. 19,20 Similarly, a comparable prevalence (25%) had been reported by Mongardon N. 20 Moreover, we learned that 47.1% of patients who suffered moderate and severe pain 1 month after the surgery had neuropathological agony, whereas only 10.6% of patients with mild pain had that. Meanwhile, among 29 patients who had neuropathological pain, 28 still suffered 6-month postoperative agony.…”
supporting
confidence: 82%
“…Fourth, rare complications including pneumothorax or large vessel injury could not be assessed, and larger sample sizes could be required to analyse rare incidents. Finally, ESPB and SAPB may play a signi cant role in avoiding postoperative chronic pain [48,49]. However, none of the included studies evaluated the e cacy of ESPB and SAPB for chronic pain, and more RCTs and longer follow-up are needed to assess the long-term e cacy of both.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TEB is regarded as the gold standard for postoperative analgesia, and TPVB is the most representative region block technique. Intrathoracic INB is a frequently used technique due to its safety, convenience, and accuracy [ 10 , 14 , 23 ]. These 3 methods are the most common techniques for acute pain relief after VATS, and their effects have been confirmed by numerous studies.…”
Section: Discussionmentioning
confidence: 99%